Re-framing risk transfer to assess integrative partnership opportunities: the S.A.R. approach and the AIG/BID/CNO regional surety bond facility of 2007 - Mckellar Junior, Tem C. (2008)
The identification, allocation and management of project risks are major concerns to in establishing and administering public-private partnerships (PPP). Consequently managers of public entities, development banks, construction companies and insurers are studying and employing many techniques to address the assessment and management of project risks. Risk transfer is a hallmark of the purported benefits provided by PPP, yet due to contractual and conceptual realities, the public party (the ceding entity) almost always remains the ultimate risk bearer. Consequently, public party retains an enduring interest in the overall management of these ceded risks. This dissertation explores shortcomings of the common approaches to conceptualizing risk management in the context of a PPP. By focusing the concepts of interdependence and mutuality and using the decision to transfer project risk, this dissertation frames the decision to transfer risk in terms of: the interdependent realities of systemic relationships, broadens the technical concepts of risk and risk assessment and considers the reflective use of differences in perspective to analyze the case study. The author explores these concepts in an analysis of decision of a risk manager of the Brazilian construction company Construtora Norberto Odebrecht to design an innovative surety bond facility with the Inter-American Development Bank (BID) and an insurer, the American International Group (AIG), a deal which won recognition as Trade Finance Magazine’s 2007 deal of the year. The author argues that by framing risk transfer in terms of the organization’s systemic disposition, technical assessment and reflective dynamics, one may identify and create more opportunities to engage in successful long-term relationships in ways that current PPP literature does not yet address. The results should provide contributions for future research into project risk transfer, inter-organizational cooperation and potential project partner selection.